2022
DOI: 10.4322/acr.2021.352
|View full text |Cite
|
Sign up to set email alerts
|

Solid papillary carcinoma of the breast

Abstract: Solid Papillary Carcinoma (SPC) of the breast is a rare tumor with an incidence of less than 1%, mainly affecting elderly females. It is morphologically characterized by well-defined nodules with low-grade nuclear features associated with fibrovascular cores and shows neuroendocrine differentiation. SPC can be in-situ or invasive but has a favorable prognosis. It is a morphological mimicker of some pre-malignant conditions leading to its frequent misdiagnosis. An appropriate immunohistochemical (IHC) panel wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…The papillary carcinoma was subdivided into solid type and non-solid type, the positivity rate for solid type was 67% and for non-solid type was 8%. our findings are consistent with those of a previous study (26) wherein a significant level of chromogranin positivity was detected in solid papillary carcinoma of the breast. Former investigation (16) found that there was a significantly lower expression of chromogranin for benign papillary breast lesions than malignant papillary breast lesions (P=.05) which came in parallel to the result of our study.…”
Section: Discussionsupporting
confidence: 94%
“…The papillary carcinoma was subdivided into solid type and non-solid type, the positivity rate for solid type was 67% and for non-solid type was 8%. our findings are consistent with those of a previous study (26) wherein a significant level of chromogranin positivity was detected in solid papillary carcinoma of the breast. Former investigation (16) found that there was a significantly lower expression of chromogranin for benign papillary breast lesions than malignant papillary breast lesions (P=.05) which came in parallel to the result of our study.…”
Section: Discussionsupporting
confidence: 94%
“…Extracellular mucin production can also be seen. 4 Although Neuroendocrine differentiation has been reported in approximately half of all SPC cases in the current literature. 2,6 Not all SPC exhibit neuroendocrine differentiation.…”
Section: Discussionmentioning
confidence: 89%
“…9 The treatment protocols of SPC are still not well-established and vary from breast-conserving surgery to mastectomy depending upon the extent of the invasive component with or without adjuvant endocrine/chemotherapy. 4 In the case of our patient, neoadjuvant chemotherapy along with mastectomy was performed.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations